Kampanye Sosial Pentingnya Penggunaan Sunscreen Sebagai Upaya Pencegahan Dampak Buruk Sinar UV Terhadap Kulit Pada Remaja Usia 12-17 Tahun Di Kota Palembang - Dita Aulia; Yosef Yulius; Heri Iswandi (VisArt: Jurnal Seni Rupa dan Design, 2024)
Excessive UV rays will have a negative impact on the skin, one of the negative effects of which is sunburn and can even cause skin cancer. The main problem faced is that there are still many people who do not know the dangers of UV rays on the skin and not many people know how to prevent them. This design has the main objective, namely to carry out a campaign, namely to encourage teenagers aged 12-17 years to use sunscreen to avoid this exposure. Here using several methods, one of which is collecting data through questionnaires, the results of this collection can be concluded that there are still many people in Indonesia who underestimate the use of sunscreen, especially men who collected the largest amount of data in the questionnaire regarding why they don't use sunscreen. This UV light campaign presents a unique campaign regarding the invitation and use of sunscreen properly and correctly, as well as helping in choosing the right sunscreen for the skin.